FIELD EXPERIMENTS AND NUMERICAL MODELING OF MASS ENTRAINMENT IN SNOW AVALANCHES - Sovilla B.; Bartelt P.; Burlando P. (My University, 2006)
Snow entrainment alters the speed and hence the run-out distance of avalanches, yet little is known about this significant process. We studied entrainment in snow avalanches using observations from (1) the Swiss Vallée de la Sionne test site, (2) the Italian Pizzac site, (3) catastrophic avalanches that occurred during the winter 1998–1999 in Switzerland, and (4) a medium-sized spontaneous avalanche that occurred in 2000 in Davos, Switzerland. We determined mass and energy balances for 18 avalanche events. On average, the mass increased by a factor of 4. The primary mode of entrainment appeared to be frontal ploughing, although entrainment behind the avalanche front was also observed. Step entrainment, where a snow cover layer fractures and is entirely consumed by the avalanche, also occurred. Basal erosion was negligible. Mass availability and snow cover structure were the limiting factors governing entrainment. Other factors such as track topography and avalanche dimension played a secondary role. Using the experimental results, we introduced an entrainment model into a Saint-Venant type flow model where the internal shear deformation of the avalanche is governed by a Bagnold law and the shear stress at the basal layer is treated as a Voellmy fluid. The model with entrainment not only improves the prediction of the velocities and flow heights in comparison to measurements, but also reproduces the variations in run-out distances, which characterize avalanches with similar terminal velocities but different masses.